Beyond Illiberalism - Shepherd, Robert J., author. George Washington University, USA. Link
1 online resource (viii, 156 pages).
Keywords: Arguing that there has never been a consensus on which rights all people are entitled, Beyond Illiberalism: Rights, Rhetoric, and Reality in a Pluralistic World traces how the concept of human rights is tied to a global project rooted in colonialism and grounded in nineteenth-century liberalism and post-World War II social democratic principles. This book contends that human rights are conceived, imagined, and promoted by dominant states, organizations, and activists within a specific liberal framework, and that, after more than 200 years, the dream of a universal history rooted in the worldview of G.W.F. Hegel has been displaced by the stuff of practical reality. Robert J. Shepherd shifts our attention to rights as a matter of human practice and emphasizes the importance of the actualization of rights within local contexts, demonstrating the spuriousness of categorizing governments as "liberal" or "illiberal" based on preconceived notions of what counts as legitimate rights. This book will appeal to scholars of anthropology, sociology, socio-legal studies, and cultural studies.